The Effect of Leverage, Firm Size, and Transfer Pricing on Tax Planning in Energy Sector Companies Listed on the Indonesia Stock Exchange from 2022-2024 - Siska Dwi Febriani; F Fauziyah; Puji Rahayu (LP2M IAIN Palopo, 2026)
The purpose of this study is to examine the effect of leverage, firm size, and transfer pricing on tax planning in energy companies listed on the Indonesia Stock Exchange during the period 2022–2024. A quantitative approach using panel data regression analysis was used in this study. The regression model was selected through Chow tests, Hausman tests, and Lagrange Multiplier tests to determine the most appropriate model, with the results proving that the Random Effect Model (REM) was the most accurate model. Purposive sampling was used to obtain samples that met the research criteria during the observation period. The Effective Tax Rate (ETR) was used to measure tax planning. The results showed that tax planning was significantly influenced by leverage, with the Debt to Asset Ratio (DAR) as an indicator in the calculation, indicating that the company's funding structure through the use of debt could affect the company's tax management policy. Conversely, tax planning is not significantly influenced by firm size and transfer pricing. This situation is thought to be related to the existence of generally applicable tax regulations and strict fiscal supervision of taxation practices. The findings of this study indicate that corporate financing decisions play an important role in determining tax management strategies. This study provides empirical evidence that tax planning in Indonesian energy companies is more influenced by leverage than by firm size or transfer pricing.